The Role of Oil in Shaping the U.S. Strategy and the Mechanism for Dealing with the Oil Sector in Iraq after its Occupation - Muzahem Mejbel, Assist. Prof. Dr. Arshed (Opción, 1970)
The strategic value of oil in global politics outweighs its economic value. Neo-conservatives believe in the use of force if necessary to achieve their goals. By reviewing the U.S. war on terrorism, we find it a strategy to control Middle East oil. Oil was the main factor in the Third Gulf War, the 2003 occupation of Iraq. The articles in the 2005 Iraqi Constitution on oil are not a means of weakening Iraq's unity and creating problems. Finally, oil has played the biggest role in undermining Iraq's national security because of Iraq's vast stockpiles, as well as low extraction prices coupled with other countries.